Gaya Bahasa pada Lirik Lagu “Bertaut” Karya Nadin Amizah - Dede Fadilatunisa (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
The lyrics of "Bertaut" by Nadin Amizah are rich with stylistic devices that deepen its emotional resonance and meaning. This study seeks to analyze the figurative language present in the song, highlighting its significance as a work of musical art. The song employs a variety of linguistic elements that powerfully transmit profound emotions to its audience. Utilizing a qualitative descriptive approach and content analysis methods, this research aims to identify and interpret the figurative language within the lyrics. The findings indicate that Nadin Amizah skillfully incorporates a range of figurative techniques—such as personification, metaphor, hyperbole, and repetition—which enhance both the emotional tone and overall meaning of the song. These stylistic elements not only enrich the lyrics but also reflect the emotional bond between the writer and her mother, which serves as the song's central theme. Ultimately, this study sheds light on how figurative language can effectively convey powerful messages and foster emotional connections in musical compositions.